Pengembangan dan Analisis Validitas Alat Bantu Pembelajaran Kimia Advance Organizer Berbasis Fenomena untuk Melatih Literasi Sains Siswa SMA - Azza Nuriah Widowati; Rudiana Agustini; Suyatno (Postgraduate, University of Mataram, 2025)
Educational developments in the 21st century require students to be prepared to face global competition. This preparedness can be supported by several basic skills that are equipped to each student as the future generation of the nation, for example, science literacy. Specifically, the study aims to produce and test the validity of a phenomenon-based advance organizer learning tool consisting of a teaching module, student worksheet, textbook, and science literacy assessment instrument. The method used is RnD, with the research design chosen being Thiagarajan's 4D model, which consists of define, design, develop, and disseminate. Data were obtained from three expert validators through validation sheets and analyzed using Aiken’s V formula to determine the validity level of each component of the developed learning tools. The expected outcomes include teaching modules, student worksheets, textbooks, and science literacy questions to be applied in chemistry education. Research data was obtained from three validators using a validation sheet. The validators consisted of two lecturers from the Faculty of Mathematics and Natural Sciences at Unesa and one chemistry teacher from Puri 1 Senior High School in Mojokerto Regency. The data was analyzed based on the validity criteria of each element of the learning tools using Aiken's validation. Previously, the learning tools were reviewed by two chemistry lecturers from the Faculty of Mathematics and Natural Sciences at Unesa with the assistance of a review sheet to obtain suggestions and input. The validity data showed that the learning tools were valid, with validity data meeting the validity criteria, where the teaching module scored 0.86 on the Aiken scale, the student worksheet scored 0.86 on the Aiken scale, the textbook scored 0.89, and the science literacy questions scored 0.99. These findings indicate that the developed learning tools meet high validity criteria and are suitable for use in chemistry learning. The integration of the phenomenon-based approach with the advance organizer model provides a structured framework that helps students connect abstract chemistry concepts with real-world phenomena, thereby improving science literacy and engagement. In conclusion, the phenomenon-based advance organizer chemistry learning tool developed in this study is valid and feasible to be implemented in high school classrooms to train students’ science literacy skills, and further research is recommended to test its effectiveness in improving learning outcomes.